Numerical investigation of the flow behavior of an isothermal corner impinging jet for building ventilation. (September 2022) - Ameen, Arman; Cehlin, Mathias; Larsson, Ulf; Yamasawa, Haruna; Kobayashi, Tomohiro
Abstract: The corner impinging jet concept has been proposed as a new air distribution system for use in office environments. The present paper reports the mean flow field behavior of an isothermal corner-based turbulent impinging jet in a room. A detailed experimental study is carried out to validate the numerical simulations, and the predictions are performed using three turbulence models. RNG k − ε model was chosen for this study. This study investigates the influence different configuration parameters such as jet discharge height, diffuser geometry (shape and size) and supply airflow rate have on the flow field. The results show that the diffuser geometries used in this study had in general a minor effect on the velocity developments along the centerline of the floor, maximum velocity decay and jet spreading rate except for some specific cases. When evaluating the triangle geometry cases, the results show that all the cases with volume flow <20 L/s are able to meet Boverket's building regulations velocity requirement both for summer and winter. The applicability evaluation show that the results can be considered for room sizes between ≈25 and 100 m 2 . In addition, the wall confinement effect (90° vs. 180°) is having a significant impact on the maximum velocity decay for corner impinging jet ventilation. In the regression analysis the results shows that the distance along the diagonal centerline of the room has the most impact on the evaluation of maximum velocity decay and jet spreading rate. Highlights: Corner impinging jet shows higher max. velocity compared to center wall placed. The most important parameter affecting jet velocity decay and spreading rate is x A The results are applicable for room sizes between 25 and 100 m 2 .